2009
DOI: 10.1136/jech.2007.070656
|View full text |Cite
|
Sign up to set email alerts
|

The neighbourhood effects of geographical access to tobacco retailers on individual smoking behaviour

Abstract: Objective: To investigate whether neighbourhood measures of geographical accessibility to outlets selling tobacco (supermarkets, convenience stores and petrol stations) are associated with individual smoking behaviour in New Zealand. Methods:Using Geographical Information Systems, travel times from the population-weighted centroid of each neighbourhood to the closest outlet selling tobacco were calculated for all 38,350 neighbourhoods across New Zealand. These measures were appended to the 2002/03 New Zealand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 41 publications
5
76
1
2
Order By: Relevance
“…The comparatively extensive area of investigation and the topicality, thoroughness and validity of the data collection are further strengths of this study. In this way we have fulfilled the stipulations of several authors who had previously questioned the validity of the data (such as selected outlets, register data or participant reports (18,21,(53)(54)(55) ) and criticized the lack of cartographic GIS mapping in similar studies (19) .…”
Section: Clustering Of Social Areasmentioning
confidence: 99%
“…The comparatively extensive area of investigation and the topicality, thoroughness and validity of the data collection are further strengths of this study. In this way we have fulfilled the stipulations of several authors who had previously questioned the validity of the data (such as selected outlets, register data or participant reports (18,21,(53)(54)(55) ) and criticized the lack of cartographic GIS mapping in similar studies (19) .…”
Section: Clustering Of Social Areasmentioning
confidence: 99%
“…It has been estimated that the contribution of tobacco smoking to inequalities in mortality increased between 1984 and 1999 from 16 to 21 percent for males, and 3 to 11 percent for females (Blakely and Wilson 2005). In addition, previous New Zealand research into smoking behavior has demonstrated that various characteristics of places including social deprivation (Moon and Barnett 2003;Pearce et al 2009), segregation (Barnett 2000), and social inequality (Barnett, Moon, and Kearns 2004;Barnett, Pearce, and Moon 2005) exert an independent influence on smoking behavior.…”
mentioning
confidence: 98%
“…The GIS has been utilized as an approach to assess differential access to substances and to examine the spatial relationships of ecological factors [50,51]. In the present study, we could quantify the availability of convenience stores around a school and explore its correlation with students' alcohol use.…”
Section: Discussionmentioning
confidence: 99%